Sympathy in Translation: Paul et Virginie on the London Stage - Calè, Luisa (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis essay explores the aesthetic boundaries of sympathy and spectatorship through James Cobb’s adaptation of Bernardin de Saint Pierre’s Paul et Virginie (1788, 1789) into a comic opera for the London stage (1800). The aesthetic reach of a story differs when it is experienced in a solitary encounter with the text on the page or a public performance of actors on the stage. The virtual spectatorship experienced in reading might invite the reader to other worlds and shape the public into a transnational community of sentiment. By contrast, theatre-goers are engaged in a different performance of fellow-feeling: much as they identify with the action on the stage, their identity is also shaped by being part of the public that comes together at the theatre, where performances take on local and national forms of collective identity. Comparing the virtual and actual forms of spectatorship posited by the French novel and the English comic opera, this essay explores how the medium of the book and the theatre construct different aesthetic communities and project different models of citizenship and colonial governance. As Cobb transposes the story from Mauritius to the West Indies, his adaptation of the plot offers an ameliorist model of slavery. Through its imagined community and its comedic ending Cobb explores the possibility that the metropolis and the colonies might be united in a creole nation within the empire.